2008
DOI: 10.2478/s11756-008-0044-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of wheat leaf rust (Puccinia triticina) races and virulence changes in Slovakia in 1994–2004

Abstract: Abstract:In 1995-2004 we investigated leaf rust virulence in Slovakia on Thatcher near isogenic lines (NILs) with genes Lr1, Lr2a, Lr2b, Lr2c, Lr3a, Lr9, Lr10, Lr11, Lr15, Lr17, Lr19, Lr21, Lr23, Lr24, Lr26 and Lr28. According to reaction of leaf rust isolates resistance genes Lr9 and Lr19 were completely effective to all examined pathotypes in all years. The resistance genes Lr24 and Lr28 were also completely effective to all examined pathotypes till the year 2001. In the year 2001 we detected 20% and 10% vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 7 publications
(4 reference statements)
1
15
2
1
Order By: Relevance
“…According to the acreage sown to a specific variety, virulent races were selected with respect to Lr13 (Goyeau et al 2006) in France and Europe (Park et al 2001). Hanzalová et al (2008) obtained similar results for Lr26 which was overcome in the early seventies by race SaBa77. Nevertheless Lr26 is present in 18 (marker confirmed) current cultivars.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…According to the acreage sown to a specific variety, virulent races were selected with respect to Lr13 (Goyeau et al 2006) in France and Europe (Park et al 2001). Hanzalová et al (2008) obtained similar results for Lr26 which was overcome in the early seventies by race SaBa77. Nevertheless Lr26 is present in 18 (marker confirmed) current cultivars.…”
Section: Discussionsupporting
confidence: 86%
“…However, Kolmer (2005) collected Lr17 virulent isolates in the prairie region of Manitoba, independent of the presence of cultivars carrying Lr17 in this region. Many studies have concluded that races with specific virulence to Lr loci exist on susceptible cultivars in low frequency dominated by the most aggressive pathotype (Kolmer 2005) and are selected by the growing acreage of race specific Lr carrying cultivars (Hanzalová et al 2008;, Park et al 2001). Hence, it may be expected that rust populations containing races virulent against Lr17 will be more frequent if the acreage of Lr17 carrying cultivars increases in Germany.…”
Section: Discussionmentioning
confidence: 96%
“…Virulence to Lr9 was found neither in the Czech Republic in 2005-2008(Hanzalová 2010 nor in Germany and in Russia in 2001-2003(Lind & Gultyaeva 2007. In Slovakia virulence to Lr9 was recorded in 2008 (Hanzalová et al 2012).…”
Section: Resultsmentioning
confidence: 96%
“…Carroll can (Hanzalová 2010). In the period 1994-2011 virulence to Lr19 was not recorded in Slovakia (Hanzalová et al 2008(Hanzalová et al , 2012. In Germany virulence to Lr19 was found in 1999 (Gultyaeva et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Diese rassen sind virulent gegenüber mehreren resistenzgenen, beispielsweise Saba 77 gegenüber Lr1, Lr2a, Lr2b, Lr2c, Lr3a, Lr3bg, Lr3ka, Lr13, Lr15, Lr17b, Lr20, Lr26 und Lr37 (goyeau et al 2006 Goyeau und Lannou (2011) untersuchten 153 von 275 anfällig, da sie die entsprechenden resistenzgene enthalten. Zahlreiche autoren, die mit in europa gesammelten isolaten arbeiten, bestätigen die im Feldversuch und blattsegmenttests festgestellte avirulenz gegenüber den resistenzgenen Lr9, Lr19 und Lr24 (goyeau et al 2006;goyeau & lannou 2011;Hanzalová et al 2008;Morgounov et al 2011). Da diese Resistenzen rassenspezifisch sind, ist jedoch bei ihrer Nutzung in Sorten zu erwarten, dass sich virulente isolate durchsetzen.…”
Section: Mikroskopische Auswertung Der Blattsegmenteunclassified